Learning acceleration for gifted students: Favorable and unfavorable arguments - Rodrigues Maia-Pinto, Renata (2012)
This paper analyzes acceleration in education as a practice for meeting the educational needs of gifted students, and points out favorable and unfavorable arguments on the use of this practice. Acceleration is an educational practice consisting of several teaching strategies designed to encourage academically gifted students and reduce their time spent in school. It promotes faster learning by matching the curriculum to the student’s level of knowledge, interest and motivation. There are several arguments in favor of acceleration, such as the improvement of academic performance, self-esteem and student’s social adjustment. However, educators are reluctant to implement this practice, arguing that students may be immature or lose part of the content of the regular curriculum.